2020
DOI: 10.3171/2020.7.focus20466
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors, comorbidities, quality of life, and complications after surgery in idiopathic normal pressure hydrocephalus: review of the INPH-CRasH study

Abstract: OBJECTIVEIdiopathic normal pressure hydrocephalus (INPH) is a dementia treatable by insertion of a shunt that drains CSF. The cause of the disease is unknown, but a vascular pathway has been suggested. The INPH-CRasH (Comorbidities and Risk Factors Associated with Hydrocephalus) study was a modern epidemiological case-control study designed to prospectively assess parameters regarding comorbidities and vascular risk factors (VRFs) for INPH, quality of life (QOL), and adverse events in patients with shunted INP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 71 publications
2
25
0
Order By: Relevance
“…Also, apathy and cognitive deficits caused by iNPH can mask depression, psychosis and behavioural problems. 6 Previous studies have shown that the psychiatric symptoms of patients with a diagnosis of depression who were later diagnosed with NPH significantly improved after shunt surgery. 7 It is thought that enlargement of the ventricular system may prepare the groundwork for the development of psychiatric disorders, such as mania, psychosis and depression, by causing ischaemic and degenerative changes in neighbouring structures and projections by causing a mass effect.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Also, apathy and cognitive deficits caused by iNPH can mask depression, psychosis and behavioural problems. 6 Previous studies have shown that the psychiatric symptoms of patients with a diagnosis of depression who were later diagnosed with NPH significantly improved after shunt surgery. 7 It is thought that enlargement of the ventricular system may prepare the groundwork for the development of psychiatric disorders, such as mania, psychosis and depression, by causing ischaemic and degenerative changes in neighbouring structures and projections by causing a mass effect.…”
Section: Discussionmentioning
confidence: 99%
“…Psychomotor retardation, apathy and anxiety symptoms that may also present at the same time with iNPH can mimic major depression. Also, apathy and cognitive deficits caused by iNPH can mask depression, psychosis and behavioural problems 6 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations